The Influence of Traditions and Cultural Norms on Girls’ School Withdrawal in Afghanistan: A Qualitative Study of Maternal Accounts - Qayuome Hareer, Diba (Université d'Ottawa / University of Ottawa, 2013)
Girls’ withdrawal from school is posing a major challenge to female literacy in Afghanistan. The aim of this research was to examine the influence of Afghan traditions and cultural norms on girls’ school withdrawal by parents or guardians in Khinjan District of Baghlan Province. To achieve this aim the accounts of 12 mothers with daughters pulled out of school were obtained through semi-structured interviews and analyzed via the theoretical lens of Existentialist Feminism and Hofstede’s Cultural Dimensions Model. The findings suggest that in order to address the problem of girls’ withdrawal from school in Khinjan, the informal communication networks that reinforce the tendency of parents/guardians, especially male ones, to withdraw the girls from school should be influenced by communication channels in the district. Grounded on Paulo Freire’s concept of dialogue for liberation, it is recommended that credible members in the community should initiate and engage in a transforming dialogue about education of girls, with Khinjanis.
Keywords: Girls' school withdrawal; Traditions and cultural norms; Hoftstede's Cultural Dimensions Model; Existentialist Feminism Theory